Development and Performance Analysis of Bisection Method-Based Optimal Path Length Algorithm for Terrestrial Microwave Link - Constance, Kalu (Review of Computer Engineering Research, 2019)
In this paper, Bisection method-based algorithm for the computation of optimal path length of terrestrial microwave link is presented. Also, performance analysis of the algorithm is presented in terms of the convergence cycle of the algorithm. The impact of various link parameters on the convergence cycle of the algorithm is also presented. Mathlab program was used to carry out sample numerical computation for a microwave link having the following parameters: frequency (f) = 12 GHz, transmit power (P_T) = 10dBm, transmitter antenna gain (G_T) = 35 dBi, receiver antenna gain (G_R) = 35 dBi, fade margin (〖fm〗_s) =20dB, receiver sensitivity (P_S) = -80dBm, Rain Zone = N, point refractivity gradient (dN1) = -400, link percentage outage (po)=0.01% . The results showed that the Bisection algorithm converged at the 17th cycle. It was found from the analysis that the convergence cycle of the algorithm varied linearly with frequency, decreasing with frequency from a value of 17 at frequency of 12 GHz to 15 at a frequency of 45 GHz. On the other hand, the convergence cycle varied nonlinearly with percentage availability of the link. Also, for a given frequency and link percentage availability the convergence cycle increased with increase in rain rate. The result of the research is very essential for microwave link designers to determine the optimal path length for effective link performance under different link configurations and locations.